2021
DOI: 10.3390/ijerph182312392
|View full text |Cite
|
Sign up to set email alerts
|

Visual Size Matters: The Effect of Product Depiction Size on Calorie Estimates

Abstract: Consumers’ calorie estimates are often biased and inaccurate. Even the presence of relevant nutritional information may not suffice to prevent consumer biases in calorie estimation. The current work demonstrates across two studies that visual cues given by larger product depictions lead to increased calorie estimates. Further, it demonstrates that these effects occur even when consumers are given, and notice, information about product quantity. The findings thus shed light on a novel biasing effect on consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 143 publications
(216 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Waber et al (2008) showed that price affected the therapeutic efficacy of medications due to the association between (higher) price and product efficacy. In the food domain, research has shown that visual cues that imply larger food size (e.g., larger packaging images) increase people's judgment of the food's caloric value, because size is associated with caloric content (Tal et al, 2021). More closely related to taste, seeing food products in motion was found to enhance their taste due to the perceived association of motion with freshness (Gvili et al, 2017).…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…Likewise, Waber et al (2008) showed that price affected the therapeutic efficacy of medications due to the association between (higher) price and product efficacy. In the food domain, research has shown that visual cues that imply larger food size (e.g., larger packaging images) increase people's judgment of the food's caloric value, because size is associated with caloric content (Tal et al, 2021). More closely related to taste, seeing food products in motion was found to enhance their taste due to the perceived association of motion with freshness (Gvili et al, 2017).…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%